A Literature Review: Intrusion Detection Systems in Internet of Things. (April 2020) - Chauhan, Anamika; Singh, Rajyavardhan; Jain, Pratyush
Abstract: Internet of Things (IoT) is a new and surging technological advancement where in which the Internet is connected to various day-to-day physical objects belonging to various domains and making them "smart" like that of various machine dependent processes, manufacturing processes and healthcare. It is a system of interrelated computing devices, machines and people. Internet-connected IoT devices brings several benefits in our daily life but are susceptible to security issues. These vulnerabilities to IoT systems create security threats for any smart environment formed around the aforementioned concept. Thus, there is a need for intrusion detection systems (IDSs) which are designed specifically for IoT systems in order to combat these security related threats and create a secure network for the smart environment. IoT devices tend to have limited computing and storage capabilities. Hence, conventional IDSs might not be suitable for such networks. Due to the specifications and protocols of IoT devices, intrusion detection in IoT systems proves to be a challenging task. Thus, the field of intrusion detection systems in IoT systems is one that requires research and considerable effort to address the key security issues and security threats. A literature review is presented on the IDS in IoT topic, with emphasis on the present-day research, challenges and future directions.